Merton model as predictor of failure probability of public banks in Indonesia - Firman Pribadi; Susanto Susanto (Journal of Economics, Business, and Accountancy Ventura, 2014)
This research attempts to use Black-Schole-Merton (BSM) model based on market approach to predict default probability of publishing bank in Indonesia. This is done by using stock prices and financial report. In this effort, this study estimates the neutral risk and default probability for the publish bank. The result showed that option model can predict default status more with accurate event long before default information was published for public. It can be studied from the case of Bank Century that has been imposed as a failure bank, in which it is known as bailout bank by the Indonesian government. The model does not only provide the ordinal ranking for the bank sample but also the good early warning prediction for the public. The probability estimation based on the option model can be an innovative model to measure and manage credit risk on the future for predicting probability default in Indonesia.